2019
DOI: 10.3390/ijerph16183498
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Physical Activity in Children and Adolescents with Type 1 Diabetes in Relation to the Healthy Comparators and to the Method of Insulin Therapy Used

Abstract: Given the fact that physical exertion leads to blood glucose fluctuations, type one diabetes mellitus (T1D) may potentially constitute a barrier for obtaining a sufficient amount of exercise. The main purpose of the study was to compare the level of physical activity between children with T1D (n = 215) and healthy controls (n = 115) and to assess the physical activity of the study group in relation to the applied method of insulin therapy, i.e., the use of insulin pen vs. insulin pump. The level of physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 42 publications
3
35
0
4
Order By: Relevance
“…There are currently no other cross-sectional data comparing lockdown PA levels between adolescents with T1D and healthy controls. Pre-pandemic data, however, indicates that adolescents with T1D tend to be less active than their peers [ 14 , 15 , 16 ], and studies of individuals with T1D during lockdown without a control group indicate that their PA levels were lower than usual [ 34 , 35 , 36 ]. While it was encouraging to find that those with T1D exercised at a similar level to their peers without diabetes during the lockdown period in our study, the average PAQ score of 2.36 for all participants was well below the estimated cut-off of 2.75 for meeting minimum recommended levels of MVPA [ 31 ], with approximately two-thirds failing to meet this threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently no other cross-sectional data comparing lockdown PA levels between adolescents with T1D and healthy controls. Pre-pandemic data, however, indicates that adolescents with T1D tend to be less active than their peers [ 14 , 15 , 16 ], and studies of individuals with T1D during lockdown without a control group indicate that their PA levels were lower than usual [ 34 , 35 , 36 ]. While it was encouraging to find that those with T1D exercised at a similar level to their peers without diabetes during the lockdown period in our study, the average PAQ score of 2.36 for all participants was well below the estimated cut-off of 2.75 for meeting minimum recommended levels of MVPA [ 31 ], with approximately two-thirds failing to meet this threshold.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparative data is not available for young people with T1D in NZ. A number of studies worldwide have found that young people with T1D are typically less active and spend more time engaging in sedentary behaviours than their peers without the disease [ 13 , 14 , 15 , 16 ]. Furthermore, the majority of adolescents in the general population do not achieve the recommended levels of PA. An estimated 81% of students aged 11–17 years worldwide are insufficiently physically active [ 17 ], and in NZ, only 7% of young people aged 5–17 reported achieving PA guidelines in a nationwide survey [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that children with T1D also spend less time in physical activity than healthy individuals 15,16 . They fear experiencing hypoglycemia during and after exercise, given the negative effects of the condition 15,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that children with T1D also spend less time in physical activity than healthy individuals. 15,16 They fear experiencing hypoglycemia during and after exercise, given the negative effects of the condition. 15,17,18 It has been reported that presenting the benefits of physical activity to children with T1D will help lessen their fears.…”
mentioning
confidence: 99%
“…The minimum size of the sample was calculated taking into account the number of children with intellectual disability attending the special educational facility in the Podkarpackie Region, Poland, annually. A fraction size of 0.9 was used, with a maximum error of 5% [ 32 , 33 , 34 , 35 ], a sample size of 58 children was obtained. The study involved 60 children.…”
Section: Methodsmentioning
confidence: 99%